2022
DOI: 10.32665/james.v6i1.887
|View full text |Cite
|
Sign up to set email alerts
|

Metode Fuzzy Time Series Logika Ruey Chyn Tsaur untuk Prediksi Pola Data Trend Naik

Abstract: Transportasi kereta api berkembang dari waktu ke waktu sesuai kebutuhannya. Terutama Infrastruktur transportasi yang berperan penting dalam mendukung mobilisasi dan aksesbilitas baik orang maupun barang dari tempat lain menuju ke suatu tempat tertentu sehingga menimalisir kesenjangan pada seluruh wilayah. Perbaikan transportasi khususnya kereta api diharapkan adanya pergeseran pertumbuhan, mempercepat pengembangan suatu daerah dalam wilayah. Jumlah barang yang diangkut melalui transportasi kereta perlu dipredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Lastly, Fuzzy Time Series is found in research [14- [20]. Further research by [19] in 2022 regarding the Analysis of Palm Oil Consumption and Production in Indonesia Using the Moving Average Method. Based on forecasting research, results showed that palm oil consumption in Indonesia 2022 will increase by 10.36% or 1.643 million tonnes compared to total palm oil consumption in 2021, which was only 15.857 million tonnes.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Fuzzy Time Series is found in research [14- [20]. Further research by [19] in 2022 regarding the Analysis of Palm Oil Consumption and Production in Indonesia Using the Moving Average Method. Based on forecasting research, results showed that palm oil consumption in Indonesia 2022 will increase by 10.36% or 1.643 million tonnes compared to total palm oil consumption in 2021, which was only 15.857 million tonnes.…”
Section: Introductionmentioning
confidence: 99%